2022
DOI: 10.3758/s13414-022-02473-8
|View full text |Cite
|
Sign up to set email alerts
|

Can faces affect object-based attention? Evidence from online experiments

Abstract: This study tested how human faces affect object-based attention (OBA) through two online experiments in a modified double-rectangle paradigm. The results of Experiment 1 revealed that faces did not elicit the OBA effect as non-face objects, which was caused by a longer response time (RT) when attention is focused on faces relative to non-face objects. In addition, by observing faster RTs when attention was engaged horizontally rather than vertically, we found a significant horizontal attention bias, which migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 78 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…This ensured that no visible faces were presented on the screen when participants shifted their attention to the second target, hence eliminating (or at least dramatically reducing) any direct filtering cost. Noteworthy, previous findings showed that the OBA effect persists after a short period of object disappearance (Xie et al, 2021 ). Based on this evidence and in line with H3 we predict that the disappeared faces should elicit a significant OBA effect both in faces and in the mosaic objects.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…This ensured that no visible faces were presented on the screen when participants shifted their attention to the second target, hence eliminating (or at least dramatically reducing) any direct filtering cost. Noteworthy, previous findings showed that the OBA effect persists after a short period of object disappearance (Xie et al, 2021 ). Based on this evidence and in line with H3 we predict that the disappeared faces should elicit a significant OBA effect both in faces and in the mosaic objects.…”
Section: Methodsmentioning
confidence: 90%
“…In this way, we ensured eliminating (or at least dramatically reducing) any stimulus-specific filtering cost on attentional shifting. Furthermore, based on a finding that objects can still elicit the OBA effect after their short period of offset (Xie et al, 2021 ), we predict that the OBA effect would be observed for faces that disappear for a short period (H3).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations